Long-Term Outcomes of Children and Adolescents With Postural Tachycardia Syndrome After Conventional Treatment - Tao, Chunyan; Lu, Wenxin; Lin, Jing; Li, Hongxia; Li, Xueying; Tang, Chaoshu; Du, Junbao; Jin, Hongfang (Frontiers in Pediatrics, 2019)
Objectives: To explore the long-term outcomes of children and adolescents with postural tachycardia syndrome receiving conventional interventions. Materials and Methods: A total of 121 patients were recruited, but 6 (5.0%) of them were lost at follow-up. The detailed clinical data were collected, and the reoccurrence and frequency of orthostatic intolerance symptoms were evaluated with a mean followed-up period of 18.7 months (range, 14-74 months). The Kaplan-Meier curve was used to show the cumulative symptom-free rate of patients over time. Factors influencing the long-term outcomes were examined using the Cox’s proportional hazards models. Results: The cumulative symptom-free rate was gradually increased over time. It was 48.4% at the 1-year follow-up and increased to 85.6% at the 6-year follow-up. The duration of symptoms before treatment and the maximum upright heart rate in standing-up test were identified as independent indicators for the long-term outcomes. Each 1-month prolongation in the duration of symptoms before treatment was associated with a 1.2% decrease in the cumulative symptom-free rate. However, each 1-bpm increase in the maximum upright heart rate in standing-up test was associated with a 2.1% increase in the cumulative symptom-free rate. Conclusions: The long-term outcomes of postural tachycardia syndrome patients who received conventional interventions are benign and the cumulative symptom-free rate was gradually increased over time. The prolonged duration of symptoms before treatment and the reduced maximum upright heart rate in standing-up test are the independent risk indicators.